Challenges of the deaf and hearing impaired in the masked world of COVID-19 - Suneela Garg; Chetana Prakash Deshmukh; Meghachandra M Singh; Amod Borle; Blake S Wilson (Wolters Kluwer Medknow Publications, 2021)
Difficulties of the hearing impaired have increased due to COVID-19, leading to lack of inclusiveness along with the breakdown of their mental, physical, and social health. The study objective was to assess the challenges faced by the deaf and hearing-impaired people during COVID-19 by a literature review. Literature search was done using keywords such as "challenges" OR "barriers" and "COVID-19" OR "Deaf" OR "Hearing Impaired" OR "Communication" on PubMed and Google Scholar from November 2019 to June 2020. The challenges faced were lack of information, face mask making communication difficult, social distancing affecting their physical, mental health, stigma and barriers related to the health-care system. Strategies included use of technology, help from sign language instructors, and preparedness of health-care settings for the hearing disabled. System strengthening, tele-medicine, and policy amendments can be the pillars to build up the support system for the hearing impaired to protect them from COVID-19.